Clinical laboratory reference ([Medical laboratory observer], 1974)
Annual. Laboratory products and services currently available in the United States. Product information section arranged alphabetically by companies. Entries include description and ordering information. Indexes by manufactures; brand names; and test, equipment, and services. Product photograph section.
Keywords: Pathological laboratories : Equipment and supplies : Directories; Pathological laboratories : Directories; Biological apparatus and supplies : Directories; Biological apparatus and supplies; Pathological laboratories; Pathological laboratories : Equipment and supplies; Clinical Laboratory Techniques : instrumentation; Medical Laboratory Science